Mental disorders, psychopharmacological treatments, and mortality in 2150 COVID‐19 Spanish inpatients. (13th April 2021) - Diez‐Quevedo, Crisanto; Iglesias‐González, Maria; Giralt‐López, Maria; Rangil, Teresa; Sanagustin, David; Moreira, Mónica; López‐Ramentol, Maite; Ibáñez‐Caparrós, Ana; Lorán, Maria‐Eulalia; Bustos‐Cardona, Tatiana; Menéndez‐Cuiñas, Inés; Mundo‐Cid, Pilar; et al.
Abstract: Objective: To determine how mental disorders and psychopharmacological treatments before and during COVID‐19 hospital admissions are related to mortality. Methods: Subjects included in the study were all adult patients with a diagnosis of COVID‐19, confirmed clinically and by PCR, who were admitted to a tertiary university hospital in Badalona (Spain) between March 1 and November 17, 2020. Data were extracted anonymously from computerized clinical records. Results: 2, 150 subjects were included, 57% males, mean age 61 years. History of mental disorders was registered in 957 (45%). Throughout admission, de novo diagnosis of mood or anxiety, stress, or adjustment disorder was made in 12% of patients without previous history. Delirium was diagnosed in 10% of cases. 1011 patients (47%) received a psychotropic prescription during admission (36% benzodiazepines, 22% antidepressants, and 21% antipsychotics). Mortality rate was 17%. Delirium during admission and history of mood disorder were independently associated with higher mortality risk (hazard ratios, 1.39 and 1.52 respectively), while previous year's treatments with anxiolytics/hypnotics and antidepressants were independently associated with lower mortality risk (hazard ratios, 0.47 and 0.43, respectively). Conclusion: Mental symptoms are very common in patients hospitalized for COVID‐19 infection. Detecting, diagnosing, and treating them is key to determining the prognosis of the disease and functional recovery.